Exploring Public Sector Resilience to Emerging Events - Nabulsi, Fadi (2021)
There are certain challenges that require the public sector to be more resilient in the face of emerging events. These include the fourth industrial revolution, change in economic structures, security challenges, health pandemics, and other social cohesion challenges. This study aims to explore the concept of resilience and to develop a conceptual framework for governments, public sector leaders, various governmental sectors, researchers, and other relevant stakeholders to. To achieve this purpose, the study, through a content analysis of resilience literature, defined key components of resilience in general to come up with relevant themes and concepts of resilience to draw an initial framework. This framework was then used to conduct an exploratory qualitative study via semi-structured interviews to investigate the insights of 37 subject matter experts in the public sector within UAE. As an outcome of the thematic analysis conducted, four resilience concepts, seven principles, and eight attributes of building resilience in the public sector emerged from the data. A conceptual framework incorporating these components was developed including three resilience strategies, namely, absorptive, adaptive, and transformative strategies were identified to face various emergent events. This study showed that resilience in the public sector is not a passive, reactionary attribute of organizations that enable them to survive a disruptive event. Rather, building resilience includes taking proactive steps to collaborate, monitor, anticipate, and possibly predict emergent events. Further studies are required to validate the proposed relationships between the different attributes in the framework and resilience in the public sector by conducting quantitative hypothesis testing or qualitative case-study research.